ANALISA HUBUNGAN FAKTOR PREDISPOSISI PENDUKUNG DAN PENGUAT DENGAN KEIKUTSERTAAN IBU PASANGAN USIA SUBUR UNTUK TES-IVA DI WILAYAH KERJA PUSKESMAS HELVETIA KECAMATAN MEDAN HELVETIA TAHUN 2016 - zakiah ibhan lubis; Sori Muda .; Rasmaliah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
AbstractCervical cancer is the first killer of cancer suffered by women. In 2013 cases of cervical cancer were the highest in Indonesia 98 692 cases (0.8 ‰). One of the government's attempts to perform early in cervical cancer is through cervical cancer screening by using IVA method (Visual Inspection with Acetic Acid). Puskesmas Helvetia is one of the health centers that provide services IVA, but less response from the public. This study of the research was to analyze the relation between predisposing, enabling, and reinforcing factor with the participation mother of fertile age couple (PUS) for test-IVA at the Puskesmas Helvetia in 2016. This type of research cross-sectional study. The research was conducted in July 2016. The population is all mother of fertile age couple (PUS) who visited in Puskesmas Helvetia with a sample of 100 people. The data were gathered by conducting interviews using a questionnaires and analyzed by using the chi-square with 95% CI. The results of research showed that mother of fertile age couple did IVA is 34 people (34.0%) and a mother who did’nt IVA is 66 people (66.0%). Statistically predisposing factors such as knowledge with p-value 0.001 (RP; 5.903) and attitude with a P-value of 0.001 (RP; 3.665), reinforcing factors is exposure information with p-value of 0.001 (RP; 3.955), support the husband with p-value 0.001 (RP; 5,218) and support of health care providers with a p-value of 0.001 (RP; 10.889) had a significant association with mother of fertile age couple participation to IVA test in Puskesmas Helvetia. Recommended thet Puskesmas Helvetia to improve health education and health promotion goals of expanding early detection methods IVA cervical cancer, not only in the mother of fertile age couple but also involves the husband to support the wife to join participation  IVA method test at the Puskesmas Helvetia. Keywords : Predisposition, Enabling, Reinforcing Factor, Participation, IVA Method